Islamic Educational Parenting Styles for Children from Broken Homes in Building Life Skills at the Yatim Putra Islam Orphanageof Yogyakarta - Wantini; Rambe, Mgr Sinomba; Doli Jaya Ritonga, Raja; Al Arif Rambe, Baringin; Anis Amanullah, Wahyu (Universitas Islam Negeri Raden Intan Lampung, 2025)
Children from broken homes often experience significant psychological and social challenges, including tendencies toward introversion, limited social interaction, low self-esteem, and behavioral issues. Without appropriate intervention, these conditions can impede their personal growth and future potential. Islamic education-based parenting offers a promising approach to addressing these issues by promoting moral development and essential life skills. This study aims to explore the Islamic parenting strategies implemented at the Yatim Putra Islam Orphanage in Yogyakarta and examine how these strategies contribute to the development of life skills among children from broken home backgrounds. Employing a qualitative case study approach, data were collected through in-depth interviews with caregivers and children, participant observation, and document analysis. The data were analyzed using Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing. The findings reveal that the orphanage adopts several Islamic parenting styles: loving parenting (applied to informant P), exemplary parenting (to informants P and A), advice-based parenting (to informant A), supervisory parenting, and corrective or disciplinary parenting (to informant R). Regarding life skills development, the institution successfully enhances personal skills such as self-confidence and independence (informant P), social skills like communication and cooperation (informants P and A), and vocational skills relevant to self-sufficiency (informant R). These outcomes suggest that a structured Islamic educational parenting approach can effectively support the psychological, social, and practical development of children from broken homes.